Suggested role-play activities to develop cognitive skills among disadvantaged preschool fast learners - Nava, Lucina Laroya 1946-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1977)
Role-play, an activity in which the child undertakes a make believe role and expresses it in imitative action and/or verbalization, has been found in a number of studies to be an effective tool in developing cognitive skills among disadvantaged learners. The fifteen suggested role-play activities were tried out with 18 disadvantaged preschool fast learners for one and a half months. From the try-out, it could be deduced that role-play activities can help develop cognitive skills such as labeling, identifying, classifying, discriminating and categorizing which are very essential to conceptualization. Concommitantly, role-play technique also develops the affect as youngsters empathize with the different characters in the role-play situation.
Vita.
Thesis (Master of Arts in Teaching Special Education)--University of the Philippines, Diliman
Keywords: Role playing in children -- Philippines -- Quezon City; Early childhood special education -- Philippines -- Quezon City; Poor children -- Education (Preschool) -- Philippines -- Quezon City; Education, Preschool -- Activity programs -- Philippines -- Quezon City